2021
DOI: 10.2478/hukin-2021-0071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training on Soft and Hard Surfaces for Improving Running Economy

Abstract: The present study investigated the effects of plyometric jump training on hard and soft surfaces on running economy (RE), maximal oxygen uptake (VO2max), running performance and the rate of force development in orienteers. Nineteen orienteers (11 women and 8 men, body mass 61.1 ± 7.3 kg, age 21 ± 5.8 yrs) were randomly stratified based on sex, age, VO2max and RE to plyometric jumping training (8 sessions over 4 weeks) on either a hard or a soft surface. RE, VO2max and running performance were assessed on a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The high Achilles tendon stiffness could in turn be an adaptation to the numerous hills included in most training runs, as uphill running requires a larger force production of the calf muscles, and thus would be expected to lead to larger increases in tendon stiffness. It can be speculated that the lower V̇O 2 max relative to fat free mass of the new world-record holder, as opposed to the previous record holder might also have contributed to the better running economy because previous studies have observed trade-offs between V̇O 2 max and running economy ( Fletcher et al, 2009 ; Shaw et al, 2015 ; Lannerstrom et al, 2021 ). The mechanistic explanation for this trade-off is that a higher oxidative phosphorylation associated with a higher V̇O 2 max leads to an increased production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high Achilles tendon stiffness could in turn be an adaptation to the numerous hills included in most training runs, as uphill running requires a larger force production of the calf muscles, and thus would be expected to lead to larger increases in tendon stiffness. It can be speculated that the lower V̇O 2 max relative to fat free mass of the new world-record holder, as opposed to the previous record holder might also have contributed to the better running economy because previous studies have observed trade-offs between V̇O 2 max and running economy ( Fletcher et al, 2009 ; Shaw et al, 2015 ; Lannerstrom et al, 2021 ). The mechanistic explanation for this trade-off is that a higher oxidative phosphorylation associated with a higher V̇O 2 max leads to an increased production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the new world record holder would show a better running economy than his predecessor as the new world record holder completed a high training volume that in turn may improve running economy ( Barnes and Kilding, 2014 ). We also hypothesized that the new record holder would have a similar or lower than his predecessor, because other studies have shown a tradeoff between running economy and ( Fletcher et al, 2009 ; Shaw et al, 2015 ; Lannerstrom et al, 2021 ). Moreover, we also document the training characteristics of the athlete in an attempt to determine what attributes of training may have contributed to the exceptional performance.…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, a force can hit a sphere under the opponent's feet on the flat ground, but it will be bounced off on the plateau. 12 To ensure a hit, you must reduce the force of the shot to shorten the shot's range. There is no guarantee that the initial length of the muscle at the limited rocker amplitude will reduce the strength of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…None of the included studies analyses the timing of utilization of hard and soft surfaces within the athletes' preparation phase. Although we can clearly infer the best time to use with different surfaces from the results of some studies (Ramírez-Campillo et al, 2013;Arazi et al, 2014;Ahmadi et al, 2021;Jacobs et al, 2021;Lannerstrom et al, 2021;Pereira et al, 2022). It would be interesting for future research to identify which type of surface can be the best choice according to the phases of the annual plan (general preparation, specific preparation, or competition phase).…”
Section: Main Criticisms and Observations Regarding Training Programsmentioning
confidence: 97%